2004
DOI: 10.1089/108076804773710849
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Liposome-Encapsulated Acyclovir with Acyclovir Ointment: Ocular Pharmacokinetics in Rabbits

Abstract: A positively charged liposomal formulation for topical administration of acyclovir (ACV) was investigated in comparison with a commercial ACV ointment, by determining the pharmacokinetic profile of the drug in the aqueous humor of rabbits after topical administration. The ointment was tested at two different strengths: undiluted (3.0%) and diluted to the same ACV concentration as the liposomal vehicle (0.12%). A liquid formulation containing ACV plus "empty" liposomes and an isotonic aqueous ACV solution were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…PECA nanospheres in topical applications [36], Eudragit microparticles [26], or liposomes) [19]) have been successful in extending drug release time and therefore availability. However, in vivo applications are still proble-matic as both drugs and their carriers are rapidly cleared from the ocular surface by tearing and blinking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PECA nanospheres in topical applications [36], Eudragit microparticles [26], or liposomes) [19]) have been successful in extending drug release time and therefore availability. However, in vivo applications are still proble-matic as both drugs and their carriers are rapidly cleared from the ocular surface by tearing and blinking.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo applications are still proble-matic as both drugs and their carriers are rapidly cleared from the ocular surface by tearing and blinking. Hence, incorporation of carriers into a retentive ophthalmic ointment [19] or into contact lenses [22] have been proposed as means of extending drug availability to the ocular surface. However, to remedy HSV-induced vision loss, instead of treating the cornea with drugs and performing allograft surgery as two separate modalities, both with limited success rates, our results indicate that it would be possible to incorporate the drug/carrier directly into biosynthetic substitutes of human donor corneas [11,12], to allow for the drug to be released after implantation to prevent viral re-activation and re-infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000, Law et al [50] demonstrated improved corneal deposition with the cationic acyclovir-containing liposomes, compared to either the anionic or unencapsulated modalities. The liposome-encapsulated acyclovir was demonstrated to have better delivery than the commercial acyclovir ointment, at different concentrations, in rabbit model and in vitro release tests [51] . The authors postulated that the nonspecific ionic interactions increase the precorneal residence time by forming a more intimate and complete coating of the negatively charged corneal surface.…”
Section: Liposomesmentioning
confidence: 97%
“…The osmolality of the preparation was adjusted to physiological values with sodium chloride, and pH was 6.5 [25].…”
Section: Preparation Of Acyclovir Formulations For Biological Studiesmentioning
confidence: 99%